Método de referência para geração do portfólio de oportunidades de inovação - Cavalcante, Marcia Beatriz (2012)
In the context of business organizations, there is an on-going need of products and services launch on a regular basis due to time to market shortening which has been taking better choices in portfolio decisions on innovation opportunities. In particular, the issues of portfolio has been considered primarily in product and project management, which usually occurs late in the product development process (PDP) focused on reviewing and managing the portfolio of products and projects. Therefore, there is a gap between the generation of innovation opportunities and its implementation as products or projects, which affects organizations in several aspects as identifying and valuing their innovations, detecting opportunities in earlier stages such that they can be turned into innovations, balancing choices among several criteria including non-financial as well as driving portfolio decisions from strategy. In order to overcome these difficulties, since there are a lack of methods and techniques that addresses the portfolio more broadly, this research goal was to propose a reference method for portfolio generation for innovation opportunities (MERGE-OI), which has enabled business organizations to create and select a portfolio of innovation opportunities with more assertiveness, whatever the size and market segmentation. The MERGE-OI was applied in five representatives enterprises on three economic sectors: food and beverage, construction and electronics. A field survey allowed the method to be validated in terms of consistency and coherence. Regarding the research method, this research is primarily observational and content analysis, an the same methods were employed as well as techniques, which consolidated the research development in seven major steps: each of with two main phases: pre-analysis and exploration, consolidating a research corpus based on documentary and research techniques. The three main results obtained were: the reference method MERGE-OI (activity diagrams, inputs, outputs, documents and architecture), the validation of MERGE-OI according to criteria such as usefulness and precision, as well as the portfolio of innovation opportunities in the five enterprises in which MERGE-OI was applied. More broadly, this research has highlighted the importance of integration among subjects such as innovation management, product management and project management.